Foregrounds - Skovsmose, Ole. author. aut Link
VIII, 122 p.
Keywords: "Foregrounds contributes to the development of theories of learning, in particular to theories of learning mathematics. It is relevant to students, student teachers, and researchers in the field of education as well as in mathematics education. Foregrounds contains six parts. Part I provides a summary of the notion of foreground as it has developed since the author introduced the idea in Towards a Philosophy of Critical Mathematics Education. In Part II, the reader meets some students who tell us about their neighbourhood, about drug dealing, violence, and about playing football. They tell us about their teachers, about mathematics, and about what they would like their teachers to do. They tell us about their hopes, expectations, and frustrations. Part III presents the notions of intentionality and life-world as developed by Brentano and Husserl. However, in Part IV the author provides a radical reinterpretation of these two notions. He describes “real-life intentionalities” and “real-life worlds” as profoundly structured by a range of social factors. Part V is composed as a meeting between, on the one hand, the students and their experiences as presented in Part II, and on the other hand these notions of “real-life intentionalities” and “real-life worlds”. Through this meeting the author develops further the notion of foreground. The concluding part (Part VI) brings more examples as illustrations. Ole Skovsmose has a special interest in critical mathematics education. He has investigated the landscape of investigation, students’ experience of meaning, project work, mathematics education and democracy, mathematics in action, and mathematics and power. He has published more than 20 books in Danish, English and Portuguese as well as a huge number of articles. Sense has published the following books by Ole Skovsmose: Travelling through Education, In Doubt, An Invitation to Critical Mathematics Education, and Opening the Cage: Critique and Politics ofMathematics Education, which is edited together with Brian Greer.".